SILVICULTURAL AND CONSERVATION TECHNIQUES FOR Khaya grandifoliola C. DC. IN SOUTHERN NIGERIA (2014)
Khaya grandifoliola, an important economic hardwood species, has been severely depleted by overexploitation. This necessitates its ex-situ conservation and requires in-depth knowledge of nursery handlings, seed storage, in-vitro and ex-vitro propagation on which information is sparse. Therefore, silvicultural requirements for conservation and sustainable use of K. grandifoliola in some parts of southern Nigeria were investigated in this study. Seeds of K. grandifoliola were purposively sourced from forested areas of Cross River (Boki and Kutia), Ondo (Ayegunle-Akoko, Oba-Akoko and Owo) and Oyo [National Centre for Genetic Resources and Biotechnology (NACGRAB), Ibadan] states and assessed for length, width and weight. Freshly collected (Control) seeds (n=100) were tested for viability using standard procedure. Seeds (n=100) from each of the sources were planted and 30 competitive seedlings were assessed for growth characters. Seeds (n=2000) were selected and 500 each were stored for 20 weeks at Ambient Room Temperature (ART: 28.0±2.0oC), Short Term genebank (ShT: 24.0oC), Freezer (FrZ: - 6.0oC) and Long Term genebank (LgT: -17.0oC). Monthly, seeds (n=100) were randomly selected from the four storage conditions and sowed in sterilised river sand for viability test. Single node cuttings treated with Indole Butyric Acid (IBA), Napthalene Acetic Acid (NAA) and Indole Acetic Acid (IAA) at (0, 25, 50, 150 and 200 mg/L) using sand, sawdust and 1:1 sand-sawdust were assessed for macropropagation. In-vitro culture of embryo on Murashige and Skoog (MS) medium + Benzyl Amino Purine (BAP) + NAA + Adenine Sulphate (ADS) was studied. Deoxyribonucleic Acid (DNA) samples were collected from juvenile leaves of K. grandifoliola from the 30 competitive seedlings and tested for molecular genetic diversity using six Random Amplified Polymorphic DNA (RAPD) (OPD-08, OPD-11, OPD-13, OPA-18, OPD-18, and OPD-20) primers. All experiments were laid out in completely randomised design. Data were analysed using descriptive statistics and ANOVA at α0.05. Seed sources significantly affected the seed weight (0.3±0.06g at Owo to 0.5±0.11g at NACGRAB). Seed viability ranged from 88.0% at Oba-Akoko to 98.0% at NACGRAB while seedling height was 21.7±8.27 cm at Owo and 29.9±5.30 cm at NACGRAB; the number of leaves was 30.8±6.51 at Boki and 43.2±12.78 at NACGRAB. After 20 weeks, only ShT seeds had 70.0% viability compared with 98.0% for control. The highest number of roots per cutting UNIVERSITY OF IBADAN LIBRARY iii was observed in cuttings treated with 150mg/L IBA in sawdust. Embryo culture using MS + 0.05mg/L BAP + 0.1mg/L NAA + 10mg/L ADS gave the highest number of nodes (4) and root length (7.5 cm) while pure MS produced 2 nodes and 1.5 cm root length. The RAPD markers revealed genetic similarity among K. grandifoliola sources. Ninety-four scorable polymorphic bands were generated from the six primers selected for amplification. An average of 18.2 amplicon per primer was obtained giving amplification products of 4-27 with primer OPD-08 producing the highest. Viability of Khaya grandifoliola seeds was highest at 24.0oC within 20 weeks of storage, while macropropagation was best with stem cuttings treated with 150 mg/L Indole Butyric Acid in cured sawdust. The Random Amplified Polymorphic DNA markers were effective for its molecular characterisation. Keywords: Khaya grandifoliola, Morphological traits, Seed storage, Ex-situ conservation, In-vitro propagation. Word count: 500